Pemanfaatan Metode Scamper dalam Pengembangan Produk Kuliner untuk UMKM: Studi Kasus Produk Rendang Kacang - Yuliani, Nafisah; Gustina, Dian; Sakti, Essy Malays Sari (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2024)
The aim of this research is to find out how to develop culinary MSME products using the Scamper Method. This research uses a quantitative descriptive approach. Bunda's Rendang Shop located in Depok, West Java. Rendang Bunda Shop operates in the culinary sector. The product produced is beef rendang. The variables measured in this research are Strengths, Weaknesses, Opportunities and Threats of the peanut rendang product. The data analysis technique used is SWOT analysis. The results of the research show that the IFE analysis is 3.5, meaning that rendang kacang has quite good advantages, has unique and special strengths as an innovative product, and has more than enough prerequisites for further development. The results of the EFE analysis which is 3.6 means that if you look at the external business environment, Rendang Kacang has quite a large business opportunity. At the same time, there are also threats, even though the existing threats are relatively lower than the possible opportunities for development. With these results, the peanut rendang business still has the opportunity to grow. Innovation in the context of MSMEs: Innovation as the key to sustainability and growth of MSMEs. The role of innovation in increasing the competitiveness of MSMEs in the market. Impact of Innovation on MSMEs: Improved product and service quality, Product diversification to reach a wider market, Operational efficiency through process innovation. The Scamper Method is one way to develop culinary MSME products. This method can help culinary MSMEs to produce innovative and creative product development ideas. This method can be used by various types of companies, from large companies to small and medium companies. Key Words : Scamper Method, Product Development, Rendang Kacang Products